2006
DOI: 10.1197/jamia.m2158
|View full text |Cite
|
Sign up to set email alerts
|

McMaster PLUS: A Cluster Randomized Clinical Trial of an Intervention to Accelerate Clinical Use of Evidence-based Information from Digital Libraries

Abstract: A quality- and relevance-rated online literature service increased the utilization of evidence-based information from a digital library by practicing physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…28 However, emerging technology can also facilitate knowledge dissemination among health care professionals, researchers, caregivers, and patients. 29 Technologies and tools such as ACP Journal Club, McMaster KT+, and Evidence Updates are products that interpret and disseminate synthesized evidence, 30 and present the evidence in a more userfriendly way. 31 A field of research is developing in response to the need to better understand the factors that impact how clinicians use these electronic information sources.…”
Section: Research Into Knowledge Retrieval Evaluation and Knowledgementioning
confidence: 99%
“…28 However, emerging technology can also facilitate knowledge dissemination among health care professionals, researchers, caregivers, and patients. 29 Technologies and tools such as ACP Journal Club, McMaster KT+, and Evidence Updates are products that interpret and disseminate synthesized evidence, 30 and present the evidence in a more userfriendly way. 31 A field of research is developing in response to the need to better understand the factors that impact how clinicians use these electronic information sources.…”
Section: Research Into Knowledge Retrieval Evaluation and Knowledgementioning
confidence: 99%
“…The McMaster Premium LiteratUre Service (PLUS) database, a product of the McMaster Health Knowledge Refinery, contains high-quality preappraised studies [14,15]. PLUS has accumulated less than 25,000 records since 2003, whereas approximately 3.2 million records Searching only the McMaster Premium LiteratUre Service (PLUS) for new studies relevant to updating an existing review produced equivalent results to more traditional and resource-intensive literature searching.…”
Section: Introductionmentioning
confidence: 96%
“…First, despite the many promising interventions, there are few rigorous evaluations of knowledge translations interventions, particularly those designed for managers and policy makers (Mitton et al 2007;Perrier et al 2011). However, randomized controlled trials evaluating two of the databases highlighted here (EvidenceUpdates and HealthEvidence.ca) have found that efforts to provide tailored and targeted messaging about relevant research evidence increased the utilization of evidence-based information (Dobbins et al 2009;Haynes et al 2006). Second, while systematic reviews are an important tool for knowledge translation, their utility for providers, managers and policy makers can be improved by including more detailed descriptions of the interventions and ensuring they remain up-to-date.…”
Section: Resultsmentioning
confidence: 99%